2019
DOI: 10.1002/cam4.1928
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival outcomes and restoration of graft‐vs‐leukemia effect by deferasirox after allogeneic stem cell transplantation in acute myeloid leukemia

Abstract: Deferasirox is an oral iron‐chelating agent having possible antileukemia and immune modulatory effects. Few reports have evaluated deferasirox in the setting of allogeneic hematopoietic stem cell transplantation (allo‐HSCT). We investigated the impact of deferasirox after allo‐HSCT in acute myeloid leukemia (AML). Of 326 consecutive patients undergoing allo‐HSCT in remission, analysis of 198 patients not receiving deferasirox revealed the negative prognostic effect of hyperferritinemia (≥1000 ng/mL) before and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Others have also showed that elimination of iron by chelators improved outcome in different hyperferritinemic situations. For example, the oral iron chelator deferasirox improved survival outcomes and restored graft‐versus‐leukemia effect in patients with hyperferritinemia after allogeneic stem cell transplantation in acute myeloid leukemia 21 . In addition, DFO has been tried against a range of viral and parasitic infections since replication may be influenced by iron accumulation (Table 1).…”
Section: Author/year Setting Intervention Outcomementioning
confidence: 99%
“…Others have also showed that elimination of iron by chelators improved outcome in different hyperferritinemic situations. For example, the oral iron chelator deferasirox improved survival outcomes and restored graft‐versus‐leukemia effect in patients with hyperferritinemia after allogeneic stem cell transplantation in acute myeloid leukemia 21 . In addition, DFO has been tried against a range of viral and parasitic infections since replication may be influenced by iron accumulation (Table 1).…”
Section: Author/year Setting Intervention Outcomementioning
confidence: 99%
“…A pilot clinical trial showed that DFO administration prior to allo-HSCT in patients with AL or MDS resulted in good outcomes, with no death or relapse, at a median follow-up of 20 months [110]. Similarly, a retrospective observational study of 339 patients demonstrates that the oral chelator DFX significantly reduces relapse mortality and restores graft-vs-leukemia effects (GVL) after allo-HSCT in AML, which is evidenced by high proportion of NK cells and suppressed regulatory T cells in peripheral blood [111]. Importantly, studies have shown that DFX, at concentrations equal to those clinically used or even at higher ones, has no harm to the viability of normal HSCs [85, 112].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we confirmed the selectivity and safety of DFX and demonstrated that DFX had no cytotoxic effect on PBMCs obtained from healthy donors. In fact, the clinical use of DFX was reported to improve hematopoiesis in patients with myelodysplastic syndrome (MDS) and to enhance haematopoietic recovery, outcome and survival in patients after allogenic haematopoietic stem cell transplantation 42,43 …”
Section: Discussionmentioning
confidence: 99%